Analiza wskaźnikowa w controllingu sprzedaży - Iwaniec, Magdalena Anna (Ratio Analysis in Sales Controllership, 2006)
The paper treats on ratio analysis, which is important element of sales controllership. The sales development increase ratio and the share market ratio were presented among the others. The ratio system enables to plan, control and assess the company activities. The appropriate precision and frequency of calculating are essential.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 112-119